Hubungan Religiusitas dengan Prestasi Belajar pada Siswa Sekolah Menengah Atas (SMA) Kelas XI - Muliati, Riska; Irdam; Syahrina, Isna Asyri; Mutya, Mita Fani Tri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
There are so many problems that arise in adolescence, so they need special attention. Adolescence is a period of searching for identity, so many teenagers sometimes fall into juvenile delinquency. There are many factors that cause juvenile delinquency, and if not handled properly can cause decreased academic achievement. One factor that can handle it is religiosity. This research observed the student class XI of Senior High School X. The purpose of this observation is to see the correlation between religiosity and student’s achievement class XI at Senior High School X. As hypothesis, there is positive correlation between religiosities and student’s achievement. It shows when the religiosities are high, so the student’s achievement will be high. In the other hand when the religiosities are low, so the student’s achievement will be low. The population in this research are all student in ninth class (XI) at Senior High School X it totally 77 students. And the sampling technique that used is saturated sample. Subject of the research relative small, so it better to take all subject. So the research called population research. It is done because the number of population relative small and the researcher want make the generalization with very small mistake. All students at ninth class totally 77 students, so the samples in this research are 77 students. The measuring instrument that used is religiosities scale that arranged based on the theory and the documentation of student report to see study achievement. The data analyzing method that used for hypothesis testing in this research is using product moment correlation Pearson that shows (r) = 0,589 with score (p) = 0,000 (p<0,01), Means the there is significant correlation with positive between religiosities with student achievement. In conclusion the hypothesis of this research can be accepted.